Traffic Regulation Knowledge and Driving Safety Awareness in Students - Al Zahra, Nafisa Ridlo; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2025)
This research explores the impact of students' knowledge of traffic rules on their awareness and practice regarding driving safety. The primary objective was to assess whether a better understanding of traffic rules correlates with higher levels of safety conscious behavior among transportation students. This research was structured based on a quantitative approach using a survey distributed via Google Forms which displays a 20-item Likert scale questionnaire with 150 respondents. This survey aims to determine students' level of knowledge and their safety behavior in real-life scenarios. The participants were transportation students from the Road Transportation Safety Polytechnic selected to provide a representative sample of everyday passengers. Data analysis will use correlation and regressiontests to identify significant relationships between level of knowledge and safety awareness. These findings are expected to explain the importance of including traffic rules education into the school curriculum as apreventive measure against traffic-related incidents. Insights from this study are intended to support policyrecommendations, emphasizing early education regarding traffic rules to grow a safer and more responsiblegeneration of young drivers.